Society for Immunotherapy of Cancer clinical and biomarkers data sharing resource document: Volume II—practical challenges. Issue 2 (15th December 2020) - Cesano, Alessandra; Cannarile, Michael A; Gnjatic, Sacha; Gomes, Bruno; Guinney, Justin; Karanikas, Vaios; Karkada, Mohan; Kirkwood, John M; Kotlan, Beatrix; Masucci, Giuseppe V; Meeusen, Els; Monette, Anne; et al.
Abstract : The development of strongly predictive validated biomarkers is essential for the field of immuno-oncology (IO) to advance. The highly complex, multifactorial data sets required to develop these biomarkers necessitate effective, responsible data-sharing efforts in order to maximize the scientific knowledge and utility gained from their collection. While the sharing of clinical- and safety-related trial data has already been streamlined to a large extent, the sharing of biomarker-aimed clinical trial derived data and data sets has been met with a number of hurdles that have impaired the progression of biomarkers from hypothesis to clinical use. These hurdles include technical challenges associated with the infrastructure, technology, workforce, and sustainability required for clinical biomarker data sharing. To provide guidance and assist in the navigation of these challenges, the Society for Immunotherapy of Cancer (SITC) Biomarkers Committee convened to outline the challenges that researchers currently face, both at the conceptual level (Volume I) and at the technical level (Volume II). The committee also suggests possible solutions to these problems in the form of professional standards and harmonized requirements for data sharing, assisting in continued progress toward effective, clinically relevant biomarkers in the IO setting.